2021
DOI: 10.1186/s12199-021-01035-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prolonged duration of viral clearance in non-severe SARS-CoV-2 patients in Osaka, Japan

Abstract: Background We investigated factors associated with prolonged viral clearance of SARS-CoV-2 among non-severe adult patients in Osaka, Japan. A total of 706 laboratory-confirmed COVID-19 patients were enrolled in this longitudinal observational study between 29 January 2020 and 31 May 2020, across 62 hospitals and three non-hospital recuperation facilities. Methods Logistic regression analysis was performed to investigate the factors associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In this cohort, analysis of factors associated with the duration of viral shedding showed that receipt of 2-dose vaccination was the protective factor for longer viral RNA shedding. Previously identified associated factors included older age, sex, presence of comorbidity, and the receipt of steroid ( 27 30 ). We could identify some of these factors in the univariate model.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, analysis of factors associated with the duration of viral shedding showed that receipt of 2-dose vaccination was the protective factor for longer viral RNA shedding. Previously identified associated factors included older age, sex, presence of comorbidity, and the receipt of steroid ( 27 30 ). We could identify some of these factors in the univariate model.…”
Section: Discussionmentioning
confidence: 99%
“…Covid-19 patients with comorbid condition not only affect the prognosis, it also reduces the time taken for recovery. According to the study, viral clearance will take 3 days longer for one comorbidity and 4 days longer for two or more (Hoffman et al, 2021). This mainly affect the elderly compared to younger individual.…”
Section: Methodsmentioning
confidence: 99%
“…11 The duration of viral shedding may be prolonged in males, elderly, immunocompromised hosts, corticosteroid users and those with high fever, delayed hospitalization, severe or critical illnesses. 12,13 The factors that affect the clinical sensitivity or specificity of SARS-CoV-2 tests include days from symptom onset, sampling site and antigen test compared with reverse transcriptase-PCR testing. 14 A study with air and environmental samplings has shown that SARS-CoV-2 is evolving towards more efficient aerosol transmission, and loose-fitting masks provide only modest source control.…”
Section: Origin Of Sars-cov-2 and Intermediary Animal Sourcementioning
confidence: 99%
“…The duration of viral shedding may be prolonged in males, elderly, immunocompromised hosts, corticosteroid users and those with high fever, delayed hospitalization, severe or critical illnesses. 12 , 13 The factors that affect the clinical sensitivity or specificity of SARS‐CoV‐2 tests include days from symptom onset, sampling site and antigen test compared with reverse transcriptase‐PCR testing. 14 …”
Section: Covid ‐19mentioning
confidence: 99%